Helfrich walls in nematic toroidal droplets in the presence of magnetic fields - Javier Rojo-Gonzalez; Charlotte G. Slaughter; Peter J. Collings; Jay Kikkawa; Arjun G. Yodh; Alberto Fernandez-Nieves (Proceedings of the National Academy of Sciences, 2026)
We observe the formation of stable, magnetic field induced, alignment inversion walls, also called Helfrich walls, in nematic liquid crystals (NLCs) confined to a toroidal droplet with tangential anchoring at the boundaries. Walls are rare in NLCs due to their high energy compared to lower-dimensional defect structures. However, we find that Helfrich walls naturally form, transform, and migrate in this unconventional toroidal setting, generating intricate director-field configurations due to the interplay of confining geometry and external fields. Interestingly, the presence and number of point defects in the zero field nematic configuration of the toroid influences the types of walls that arise. In the absence of point defects, splay-bend walls emerge. By contrast, when a point defect pair exists on the toroidal surface, a wall not previously classified by Helfrich, and that involves both twist and splay-bend distortions, forms, and transforms. Our experiments and numerical simulations enable the quantification and elucidation of the physics behind the formation and transformation of these wall structures, extending the class of walls that were believed to occur in NLCs.